PSXIV-12 Impact of prebiotic and probiotic feed additive blends on bovine respiratory disease, E. coli O157:H7 shedding, and performance of receiving steers. (7th December 2018) - Paulus Compart, D; Anele, U; Engel, C; Vyas, D; Kim, D; Hoppe, K
Abstract: A 64-d receiving study was conducted to evaluate the effects of 3 feed additives on rate of bovine respiratory disease (BRD), fecal E. coli O157:H7 shedding, and performance of newly received steer calves. One hundred and forty-two crossbred steer calves (initial BW 295 ± 23 kg) from multiple sources (n=22) were utilized in this study. On d 0, steers were blocked by initial BW and assigned to 1 of 16 pens. Treatments consisted of basal diet with 114 g/hd/d of (1) placebo (Control), (2) direct-fed microbial blend, (3) direct-fed microbial/yeast extract blend, or (4) prebiotic/probiotic blend. No differences ( P >0.05) in BRD incidence were observed in this study. A tendency ( P =0.08) for a day by treatment interaction was observed for fecal E. coli O157:H7 prevalence with cattle consuming treatment 4 having less fecal E. coli O157:H7 on d 28 and d 56 relative to cattle on the control treatment. Dry matter intake, BW, ADG, and G:F were similar ( P >0.10) among treatments. However, variability was reduced for steers on treatments 3 and 4 relative to steers on treatments 1 and 2 for d 64 DMI (SD = 2.8, 2.3, 1.2, and 1.8 kg for treatments 1, 2, 3, and 4 respectively) and BW (SD = 41.6, 38.7, 25.9, and 25.0 for treatments 1, 2, 3, and 4 respectively) and for ADG on d 28 (SD = 0.15, 0.15, 0.08, and 0.08 for treatments 1, 2, 3, and 4 respectively) and d 64 (SD = 0.30, 0.30, 0.08, and 0.09 for treatments 1, 2, 3, and 4 respectively). Results indicate that the cattle in this trial were not high risk for BRD. Although the feed additives used in this trial did not impact steer performance, 2 of the 3 additives reduced variability in steer performance, and 1 additive reduced fecal E. coli O157:H7 shedding.